The Implementation Of STEAM In Teaching English To Enhance Critical Thinking Using The Pancasila Student Profile Concept - Bella Novita Sari; Sukma Nur Ardini; Theresia Cicik Sophia Budiman (English Language Education Department, Universitas Majalengka, 2024)
This study aims to investigate the implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning approach in English teaching to enhance critical thinking using the pancasila student profile. This study used a qualitative methodology involving 9th-grade students who participated in STEAM activities designed to enhance their critical thinking skills and the Pancasila student profile. The research uses Classroom Action Research (CAR), a qualitative approach to solve learning problems and improve outcomes. The process of implementing this research was carried out as planned, which consisted of two cycles. In the first cycle the strategy used was the delivery of learning in general, while the second cycle was a specific and specially designed learning strategy using the STEAM approach (Science, Technology, Engineering, Art, Math). Each cycle consists of four stages,planning, action or implementation, observation and reflection.The results show a significant improvement in critical thinking after participating in the STEAM activities, indicating that this teaching approach can enhancing communication and critical thinking abilities. These findings can be used to inform policies related to STEAM education in Indonesia and improve education quality through STEAM initiatives.